Sleep Instabilities Assessed by Cardiopulmonary Coupling Analysis Increase During Childhood and Adolescence - Cysarz, Dirk; Linhard, Maijana; Seifert, Georg; Edelhäuser, Friedrich (Frontiers in Physiology, 2018)
The electrocardiogram-based cardiopulmonary coupling technique may be used to track sleep instabilities. With progressing age, maturational changes during childhood and adolescence affect sleep. The objective was to assess developmental changes in sleep instabilities in a natural setting. ECGs during nighttime sleep on regular school days were recorded from 363 subjects aged 4 to 22 years (204 females). The estimated total sleep time (ETST) decreased from 598 to 445 min during childhood and adolescence. Stable sleep linearly decreased with progressing age (high frequency coupling: 70% to 48% ETST). Unstable sleep (low frequency coupling: 9% to 19% ETST), sleep fragmentation or disordered breathing (elevated low frequency coupling: 4% to 12% ETST) and wake/REM states (very low frequency coupling: 20% to 32% ETST) linearly increased with age. Hence, with progressing age the sleep of children and adolescents shortens, becomes more unstable and is more often affected by fragmentation or sleep disordered breathing, especially in the age group >13 years. It remains to be clarified whether some of the changes are caused by a social jetlag, i.e. the misalignment of body clock and social time especially in adolescents.